Association of white blood cell count to hemoglobin ratio with the life quality after laparoscopic surgery in patients with endometriosis - Shen, Weiwei; Chen, Huan; Zhou, Xiaoming; Chen, Yichen; Zhu, Jue; Zhang, Jing (Frontiers in Endocrinology, 2025)
BackgroundEndometriosis (EM) is a common hormone-dependent and chronic inflammatory disease affecting women of reproductive age, characterized by pelvic pain, infertility, and reduced quality of life. Laparoscopic surgery is a primary treatment, yet the influence of preoperative factors on postoperative outcomes remains unclear. The white blood cell count to hemoglobin ratio (WHR), a novel marker of systemic inflammation and tissue hypoxia, has shown prognostic value in surgical oncology but its role in predicting postoperative quality of life in EM patients remains to be elucidated.ObjectiveTo explore association of white blood cell count to hemoglobin ratio (WHR) with the life quality after laparoscopic surgery in patients with endometriosis (EM).MethodsData on 271 EM patients were extracted from The First Affiliated Hospital of Ningbo University in December 2016 to October 2022. Multivariate linear regression analyses were utilized to investigate the associations of WHR levels with eight health concepts in the Short-Form 36 (SF-36) scale (3-month postoperative evaluation) and evaluated through β with 95% confidence intervals (CIs). Subgroup analyses of age, body mass index (BMI), clinical stage, pathological classification, pelvic pain and lysis of adhesion were also performed. Given <1% covariate missingness, analyses used complete cases; multiple imputation would be unlikely to change the conclusions.ResultsPatients were divided into WHR tertiles (<0.04, 0.04-0.05, ≥0.05) for description; primary models treated WHR as continuous. Higher WHR was associated with lower SF-36 scores: PCS (β = -1.42, 95% CI -2.20 to -0.65), PF (-2.82, -4.06 to -1.58), RP (-2.21, -3.94 to -0.49), VT (-2.00, -3.59 to -0.41) and RE (-2.41, -4.23 to -0.59). Tertile contrasts showed similar patterns (raw P<0.05). After BH-FDR, the WHR-PCS association remained in age<40, BMI<24 kg/m², stage IV, ovary/peritoneal phenotype, no pelvic pain, and left/right adhesion + rectum-vaginal adhesion (q<0.05); other subgroups are exploratory.ConclusionHigher pre-operative WHR was associated with lower PCS at 3 months post-surgery. FDR-adjusted analyses supported the association in selected subgroups, while other contrasts were exploratory. Pending external validation and clinically meaningful cut-offs, WHR may complement existing factors for postoperative risk stratification.